Carbon observation by electron energy-loss spectroscopy and thermoelectric properties of graphite added bismuth antimony telluride prepared by mechanical alloying-hot pressing. (June 2019) - Hirota, Kenji; Takagi, Katsuhiro; Hanasaku, Kenichi; Hasezaki, Kana L.; Saito, Hikaru; Hata, Satoshi; Hasezaki, Kazuhiro
Abstract: The effects of additional graphite in (Bi0.3 Sb1.7 Te3.1 )1− x C x ( x  = 0, 0.004, 0.012, 0.032, 0.06, and 0.12) prepared by mechanical alloying followed by hot pressing were investigated. Carbon was added to obtain a low thermal conductivity via phonon scattering. The samples were examined by X-ray diffraction, scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy-dispersive X-ray spectroscopy, and electron energy-loss spectroscopy (EELS). EELS can be used to investigate the distributions of light elements such as carbon. The diffraction peaks indicated a single-phase Bi2 Te3 –Sb2 Te3 solid solution. All the specimens were p-type semiconductors and SEM and TEM images showed dense without coarse grains. Agglomeration along the grain boundaries and inhomogeneous dispersion of carbon was observed by EELS. (Bi0.3 Sb1.7 Te3.1 )0.88 C0.12 grains wrapped by carbon layers of thickness approximately 50 nm were observed. The thermal conductivity of (Bi0.3 Sb1.7 Te3.1 )1− x C x increased with increasing x . It is considered that the presence of a large amount of carbon affected the thermal conductivity of the Bi0.3 Sb1.7 Te3.1 matrix because the thermal conductivity of carbon is much higher than that of Bi0.3 Sb1.7 Te3.1 and the carbon was dispersed inhomogeneously. Bi0.3 Sb1.7 Te3.1 without additional graphite had a maximum dimensionless figure of merit ZT  = 1.1. The Z T value decreased, and varied from 0.8 to 1.0, for (Bi0.3 Sb1.7 Te3.1 )1− x C x . The results show that inhomogeneously dispersed carbon did not improve the thermoelectric properties of Bi0.3 Sb1.7 Te3.1 . Highlights: The effects of additional graphite in (Bi0.3 Sb1.7 Te3.1 )1− x C x prepared by mechanical alloying- hot pressing were investigated. Agglomeration along the grain boundaries and inhomogeneous dispersion of carbon elements were observed by EELS. (Bi0.3 Sb1.7 Te3.1 )0.88 C0.12 grains wrapped by carbon layers of thickness approximately 50 nm were observed. The inhomogeneously dispersed carbon did not improve the thermoelectric properties of Bi0.3 Sb1.7 Te3.1 .